2019
DOI: 10.1002/joc.6170
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐model analysis of climate impacts on plant photosynthesis in China during 2000–2015

Abstract: Differences, arising from differences in gross primary production (GPP) model structures and driving forces, have fuelled arguments concerning interannual changes of GPP in China since 2000. To better investigate the interannual variability of GPP and its covariance with climate factors in China, this study adopted a multi‐model analysis based on three GPP models (i.e., Terrestrial Ecosystem Carbon flux model [TEC], Breathing Earth System Simulator model [BESS], and MOD17 GPP model). The results show that annu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 70 publications
1
1
0
Order By: Relevance
“…In the deserts of the northwest, most areas of the Qinghai-Tibet Plateau, and the grasslands in central and western Inner Mongolia, the plant growing season is relatively short due to water stress and low-temperature constraints, which leads to low productivity and even the lowest GPP. Overall, GPP decreases from southeast to northwest and coastal to inland, consistent with current research results [56][57][58][59]. The spatial distribution of GPP is highly compatible with precipitation in summer, indicating that precipitation is an important factor affecting the distribution of GPP in China.…”
Section: Temporal and Spatial Distribution Of Merged Gpp In Historica...supporting
confidence: 89%
“…In the deserts of the northwest, most areas of the Qinghai-Tibet Plateau, and the grasslands in central and western Inner Mongolia, the plant growing season is relatively short due to water stress and low-temperature constraints, which leads to low productivity and even the lowest GPP. Overall, GPP decreases from southeast to northwest and coastal to inland, consistent with current research results [56][57][58][59]. The spatial distribution of GPP is highly compatible with precipitation in summer, indicating that precipitation is an important factor affecting the distribution of GPP in China.…”
Section: Temporal and Spatial Distribution Of Merged Gpp In Historica...supporting
confidence: 89%
“…The BESS GPP and ET data have been evaluated and used in many studies (Chen and Zhang, 2019;Stocker et al, 2019;Wei et al, 2019;Yan et al, 2019). 8-day BESS GPP and ET data were comprehensively evaluated by the FLUXNET2015 dataset at global scale (Jiang and Ryu, 2016), which confirmed that both 8-day BESS GPP and ET data showed comparable performance (R 2 = 0.67 and 0.62, respectively) with global FLUXNET observations (113 sites).…”
Section: Bess Gpp and Et Datamentioning
confidence: 71%